(3GdahGFO GdTfThQjI aj TQM GdefXheI GdQMHjIs - (3YHO Gddg GdTfThQis; (3GHf GdeJbfI , CHh YHO Gddg eMeO Hf Ydj Hf eMeO Hf GdMSf GdQMHj,J (B577 (3g` s ((3MSjf s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hHYO ajbhd YHO Gddg GdTfThQi bO SCdfi hdOi YHO GdhgGH Cf CTQM GdefXheI GdQMHjI aCLHJg Edi Pdc SGdckG ef GdGNJUGQ CMSf GdeSGdc bGd GdeDda QMeg Gddg JYGdi HSe Gddg GdQMef GdQMje Ci CaJJM hChdi efg s
(3BNQgG (B:s
(3aGdMGUd CQHY RhLGJ hCe hCNJGf dCe hKdGK CNhGJ dGH hGddg CYde hef CQGO GdeRjO ef gPG eY GdHMQ ai Yde GdaQGFV hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3Yde GdaQGFVs